Convergent Foraging Tactics of Marine Predators with Different Feeding Strategies across Heterogeneous Ocean Environments - Queiroz, Nuno; Vila-Pouca, Catarina; Couto, Ana; Southall, Emily J.; Mucientes, Gonzalo; Humphries, Nicolas E.; Sims, David W. (Frontiers in Marine Science, 2017)
Advances in satellite tracking and archival technologies now allow marine animal movements and behaviour to be recorded at much finer temporal scales, providing a more detailed ecological understanding that can potentially be applicable to conservation and management strategies. Pelagic sharks are commercially exploited worldwide with current concerns that populations are declining, however, how pelagic sharks use exploited environments remains enigmatic for most species. Here we analysed high resolution dive depth profiles of two pelagic shark species with contrasting feeding strategies to investigate movement patterns in relation to environmental heterogeneity. Seven macropredatory blue (Prionace glauca) and six plankton-feeding basking (Cetorhinus maximus) sharks were tagged with pop-off satellite-linked archival tags in the North Atlantic Ocean to examine habitat use and investigate the function of dives. We grouped dives of both species into five major categories based on the two dimensional dive profile shape. Each dive-shape class presented similar frequency and characteristics among the two species with U- and V-shaped dives predominating. We tested the spatial occurrence of different U- and V-shape dive parameters in response to environmental field gradients and found that mean depth and mean depth range decreased with increasing levels of primary productivity (chlorophyll ‘a’), whereas ascent velocities displayed a positive correlation. The results suggest that a planktivore and a macropredator responded behaviourally in similar ways to encountered environmental heterogeneity. This indicates fine-scale dive profiles of shark species with different feeding strategies can be used to identify key marine habitats, such as foraging areas where sharks aggregate and which may represent target areas for conservation.